2022
DOI: 10.3390/ijms23042020
|View full text |Cite
|
Sign up to set email alerts
|

New Function of Cholesterol Oxidation Products Involved in Osteoporosis Pathogenesis

Abstract: Osteoporosis (OP) is a systemic bone disease characterized by decreased bone strength, microarchitectural changes in bone tissues, and increased risk of fracture. Its occurrence is closely related to various factors such as aging, genetic factors, living habits, and nutritional deficiencies as well as the disturbance of bone homeostasis. The dysregulation of bone metabolism is regarded as one of the key influencing factors causing OP. Cholesterol oxidation products (COPs) are important compounds in the mainten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 141 publications
(197 reference statements)
0
10
0
Order By: Relevance
“…Conversely, the downregulated GPR19 data cohorts were more strongly associated with ‘Interleukin signaling’, ‘mTOR signaling’, ‘IGF-1 signaling’ and ‘Nuclear Laminopathies’. All of these diverse functions strongly converge with respect to the pathomechanisms linked to pathological aging (DNA damage—[ 73 ]; Cholesterol regulation [ 188 , 189 , 190 ]; stem cell management [ 191 , 192 ]; UPR [ 193 , 194 ]; mTOR signaling [ 195 , 196 ]; IGF-1 signaling [ 197 , 198 ]; laminopathies [ 199 , 200 ]).…”
Section: Functional Gpr19 Molecular Signaturesmentioning
confidence: 99%
“…Conversely, the downregulated GPR19 data cohorts were more strongly associated with ‘Interleukin signaling’, ‘mTOR signaling’, ‘IGF-1 signaling’ and ‘Nuclear Laminopathies’. All of these diverse functions strongly converge with respect to the pathomechanisms linked to pathological aging (DNA damage—[ 73 ]; Cholesterol regulation [ 188 , 189 , 190 ]; stem cell management [ 191 , 192 ]; UPR [ 193 , 194 ]; mTOR signaling [ 195 , 196 ]; IGF-1 signaling [ 197 , 198 ]; laminopathies [ 199 , 200 ]).…”
Section: Functional Gpr19 Molecular Signaturesmentioning
confidence: 99%
“…Different processes of cholesterol metabolism are regulated by different factors in diseases. High cholesterol levels are considered as a risk factor for atherosclerosis but are also closely related to other diseases, such as chronic kidney disease, osteoporosis, diabetes mellitus and lung diseases 23–26 . Recent studies have demonstrated that cholesterol plays an important role in pulmonary diseases 17 .…”
Section: Cholesterol Metabolism and Its Role In Copdmentioning
confidence: 99%
“…Osteoporosis (OP), commonly marked by a constant decrease in bone mass and changes in bone/skeletal tissue structure, is a common bone/skeletal disease [ 1 ]. More often than not, patients do not realize OP at the early stage until accidental fractural damages occur [ 2 ]. The pathogenesis and progression of OP might be affected by aging, genetic factors, bad living habits, and nutritional deficiency, among which, the imbalance of bone homeostasis is one of the key factors [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%